Pengembangan Pemeberdayaan Masyarakat Berbasis Potensi Lokal (Limbah Tekstil dari Pabrik) di Kecamatan Rancasari Kota Bandung - Fachruroji Fachruroji; Lilis Irmawatie (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2015)
Community empowerment in Rancasari focuses on two villages, namely Cipamokolan and Mekarjaya. This empowerment is intended to give bit of capital for community member in both villages in order to improve their skills by giving the training in making door-mats. By this training, the community is expected to acquire skills, be able to do something useful, and earn extra income. The method used is a community empowerment refers to the concept of "working with people" in order "to help people to help themselves" so that the various activities undertaken should always involve the target group. This community is still modest, so the use of simple technology that is easily understood by those likely to be readily accepted. The results obtained are they can assemble in a simple activity to acquire simple skills, namely making door-mats from textile mill waste materials. In fact, they can follow it, can make simple door-mats which can be useful for marketing and can earn extra income.